2017
DOI: 10.1002/btpr.2516
|View full text |Cite
|
Sign up to set email alerts
|

Improving the baculovirus expression vector system with vankyrin‐enhanced technology

Abstract: The baculovirus expression vector system (BEVS) is a widely used platform for the production of recombinant eukaryotic proteins. However, the BEVS has limitations in comparison to other higher eukaryotic expression systems. First, the insect cell lines used in the BEVS cannot produce glycoproteins with complex-type N-glycosylation patterns. Second, protein production is limited as cells die and lyse in response to baculovirus infection. To delay cell death and lysis, we transformed several insect cell lines wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 75 publications
0
23
1
Order By: Relevance
“…It was also reported that a vankyrin-enhanced technology improved the baculovirus expression vector system. This study found that cell lysis could be delayed and that recombinant protein yields could be increased by using cell lines constitutively expressing vankyrin or vankyrin-encoding baculovirus vectors (Steele et al, 2017). SmartBac, a new baculovirus system, was developed for large protein complex production (Zhai et al, 2019).…”
Section: Insect Cellsmentioning
confidence: 99%
“…It was also reported that a vankyrin-enhanced technology improved the baculovirus expression vector system. This study found that cell lysis could be delayed and that recombinant protein yields could be increased by using cell lines constitutively expressing vankyrin or vankyrin-encoding baculovirus vectors (Steele et al, 2017). SmartBac, a new baculovirus system, was developed for large protein complex production (Zhai et al, 2019).…”
Section: Insect Cellsmentioning
confidence: 99%
“…Expression of anti‐apoptotic proteins such as vankyrins has been shown to maintain more than 90% viability at 96 hpi in both Sf9 and Hi5 cells. [ 107 ] Similarly, the anti‐apoptotic p35 gene expression also showed a 4‐fold increase in GFP titer while maintaining the culture at more than 50% viability at approximately 120 hpi. [ 108 ] Incorporation of these advancements in the AAV production process and their effect on AAV yield could be of potential interest in the future.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For many years the baculovirus expression vector system (BEVS) has been successfully employed to produce large amounts of recombinant protein in insect cells [1113]. The BEVS was further improved over time to more easily and faster generate recombinant baculovirus [14], by the elimination of viral protease genes [15], achieving higher viability during expression [16] and the option to insert multiple expression cassette into one vector-backbone [17]. In general, BEVS is considered safe as baculovirus cannot replicate in humans [18].…”
Section: Introductionmentioning
confidence: 99%